Responde Aí

Enunciado

Efetue

a )   1 + i 3 + 1 - i 3

b )   1 + i 3 1 - i 3

c )   1 + i 3   1 - i 3

Passo 1

Falaaa, blz????? Vamos começar pela letra a, apenas abrindo os termos ao cubo:

a )   1 + i 3 + 1 - i 3 = 1 + i 3 + 3 i + 3 i 2 + 1 - i 3 + 3 i 2 - 3 i

= 2 + 6 i 2 = 2 + 6 - 1 =   - 4

Passo 2

b) 1 + i 3 1 - i 3 = 1 + i 1 - i 3

Usaremos que a + b a - b = a 2 - b 2

1 + i 1 - i 3 = 1 2 - i 2 3 = 1 - - 1 3 = 8

Passo 3

c)   1 + i 3   1 - i 3 = 1 + i 1 - i 3

Usaremos que:

1 + i 1 - i =   ( 1 + i ) ( 1 + i ) ( 1 - i ) ( 1 + i ) =   1 + i + i + i 2 1 + i - i - i 2 = 2 i 2 = i

Logo

1 + i 1 - i 3 = i 3 = - i

Resposta

a ) - 4

b )   8

c ) - i